Effect of CNP additive to diluents during capacitation on live percentage and pH of bull epididymal spermatozoa. - J. Ghafil, Mohammedali; W. Zaid, Nazih; S. Ibrahim, Najlaa; F. Nema, Hayder (International Journal of Psychosocial Rehabilitation, 2024)
Abattoir male gonads specimens were collected from Al-Shoáalla abattoir from June 2019until November 2019 in an average of 2 visits per week. This study was designed to evaluatethe optimum effect of C-type natriuretic peptide on the caudal epididymal spermatozoacharacteristics from a healthy slaughter bull. Dissected and separated the epididymis fromthe entire testicle made by a small scissor. The caudae were injected with 5-8 ml of theTCM199 media containing 100 IU/ml penicillin-streptomycin and 100 IU/ml Nystatin usingan 18 gauge needle attached toa 5-ml syringe then aspirated. After collection of Spermatozoasamples of cauda epididymis were evaluated under the light microscope has individualmotility less than 70% of were rejected. The caudal epididymal Spermatozoa samplestransported from petri dish to a 10 ml test tube containing 2 ml maturation media (TCM199)that contain 100 IU/ml penicillin-streptomycin and 100 IU/ml Nystatin; the test tubeincubated in a 5% CO2 incubator at 39 Cº for 4 hours for sperm maturation, the presence ofdistal protoplasmic droplet was the criteria of sperm maturation. Then the samples dividedinto three equal groups control one, low concentration 10-7 mol/L, and high concentration 10-6 mol/L. It evaluated the effect of C-type natriuretic peptide (CNP) during capacitation on thelive percentage and pH of bull epididymal spermatozoa. The live percentage and pH ofsperm were analyzed at 5 min, 10 min, 15 min, 30 min, 45 min, 60 min, 120 min, and 180 minfor each group. A total of 20 caudal epididymides were studied during the period of theexperiment. Evaluation of spermatozoa parameters as a stained smear for dead and alivespermatozoa was conducted in addition to pH; all results were recorded.   The pH of the semen was measured immediately after the recovery of sperms from theepididymal by using a pH litmus paper. A drop of sperms suspension on a glass slide, adrop of Eosin-Negrosin stain was added and mixed. Two smears of each sample weremade when each smear dry it was mounted immediately under coverslip using DPX; 200-400 sperms were examined in each smear on a light heated stage microscope at 40xobjective power. The final percentage was calculated by taking the average of two smears.The results of herein study of live percentage in bull epidydimal sperm during thecapacitation of control group indicate that the significant changes at the level of (P